BEEF EXERCISE METHOD AND WALL SHOOTING EXERCISE BASKETBALL GAME - I Made Andika Bayu (Universitas Negeri Gorontalo, 2019)
This study aims to determine the effect of BEEF training methods and wall shooting exercises on the results of shooting in basketball games for extracurricular students at vocational high school state 3 Palembang. This research is qualitative research with a kind of quasi-experimental research (One Group Pretest-Posttest Control Design). The sample in this study were basketball extracurricular students in Palembang vocational high School 3, which numbered 20 people. The test instrument used was a shooting test instrument. Analysis of the data in this study using the t-test, namely by comparing the results of the Pretest and Posttest in BEEF training and wall shooting exercises. From the data analysis, the results were obtained: it turns out that the t count is greater than the t table, t count t table = 7.17 2, 09, so Ha is accepted and Ho is rejected. Then it can be concluded that